Maintenance Of Solar Power Plants For Household Electricity Use - Geovani Tongkotou; Indy T.Kapoh; Yehudah L.G. Sariowan; Muchdar Daeng Patabo; Julianus Gesuri Daud; Stenly I.Ponnokaraeng (Jurnal Syntax Admiration, 2024)
The maintenance of solar power plants plays a vital role in ensuring the reliability and efficiency of electricity generation for household use. As renewable energy adoption increases, solar power systems offer an eco-friendly and cost-effective solution to meet residential energy demands. The findings highlight the importance of regular maintenance schedules, the use of advanced diagnostic tools, and community-based initiatives to support household users. This research aims to provide actionable insights to improve the sustainability and cost-efficiency of solar power systems in residential settings. This study employs a combination of qualitative and quantitative research methods to investigate the maintenance of solar power plants for household electricity use. The results show that the accumulation of dirt on photovoltaic panels, battery degradation, and inverter malfunctions are the main challenges that reduce system efficiency. The proposed solution includes regular cleaning, optimal battery management, and the adoption of automated monitoring technology. This research also highlights the importance of user education and community involvement in supporting solar power plant maintenance. In conclusion, effective maintenance is key to maximizing the benefits of household solar PV, reducing operational costs, and supporting the global transition to sustainable energy. The implications of this research include the development of technology- and community-based maintenance guidelines to improve system efficiency and extend the life of devices